KEANEKARAGAMAN JENIS DAN PEMANFAATAN BAMBU DI DESA LOPAIT KABUPATEN SEMARANG JAWA TENGAH ( SPECIES DIVERSITY AND UTILITY OF BAMBOO AT LOPAIT VILLAGE SEMARANG REGENCY CENTRAL OF JAVA) - Dian Setyo Putro; J Jumari; M Murningsih (Jurnal Akademika Biologi, 2014)
Lopait Semarang’s regency society own a strong interaction with bamboo. This research aims to identification species of bamboo in Lopait village, and to share information related to the ussage of the bamboo. Data collection is using explorative survey to investigate species of bamboo in Lopait village. The information related to the ussage of bamboo collected by interview. The collected data was tabulled and described. Result data of interview made in tabulation, categorized on benefits, description of benefit’s and managerial. Based on the investigation, there are 6 species of bamboos, i.e.,  apus bamboo (Gigantochloa apus), betung bamboo (Dendrocalamus asper), black bamboo (Gigantochloa atroviolacea), ampel bamboo (Bambusa vulgaris), ori bamboo (Bambusa arundinaceae), dan atter bamboo (Gigantochloa atter). Bamboo’s usage in Lopait village were categorized into 7, they were handicraft (19 speciess of handicraft), building material (3 speciess of building material), food material (1 species of food material), chemical substance (1 species of chemical substance), food wrap (1 species), firewood, and erotion resistance. Lopait’s society own good knowledge on bamboo cultivation and have ability to manage it traditionally, or create it become valuable handicrafts. Keywords : Diversity of bamboo, bamboo utility and management, etnobotany, Lopait village